Planning for computer games research and industry: a structured dialogue design approach - Gatzoulis, Christos; Loizides, Fernando; Zaphiris, Panayiotis (My University, 2016)
A games industry can help improve a country’s financial situation by increasing its GDP through the creation of many new job opportunities. Cyprus may be a suitable location for such an industry, mainly because of the high availability of graduates, and its strong service industry. In this work, results from a study on the feasibility of creating both a computer games industry and research sector are presented. Key stakeholders including students, and representatives from government ministries, academics, incubator companies and other companies were brought together to evaluate the current Cypriot economic situation, and to create a roadmap of actions required to create a successful computer games industry. The methodology included a Structured Dialogue Design Process that was used to identify requirements. The findings from this study include categories of essential requirements identified by the stakeholders. The data in this study could be used to plan for and devise a comprehensive roadmap for creating a computer games sector that includes games companies and research centers.
Keywords: Computer games; Industry initiation; Structured dialogue design; Affinity diagramming